2020
DOI: 10.1002/star.201900205
|View full text |Cite
|
Sign up to set email alerts
|

Improved Antioxidant and Antifungal Activity of Chitosan Derivatives Bearing Urea Groups

Abstract: Eight novel chitosan derivatives bearing urea groups are designed and synthesized. Fourier transform infrared spectroscopy, 1 H nuclear magnetic resonance spectrometer, and elemental analysis are performed to confirm the structural characteristics of chitosan derivatives. The antioxidant activities, including superoxide radicals' scavenging activity, 1,1-diphenyl-2-picrylhydrazyl radicals' scavenging activity, and hydroxyl radical' scavenging activity, of the derivatives are explored within different concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…[2,30,31] For derivative CACS, new peaks appearing at 1754 and 790 cm −1 are assigned to C = O and C─Cl groups respectively. [22,32] After the Schiff bases of pyridine-4-aldehyde were grafted, the absorption of C─Cl at 790 cm −1 weakens and new peaks appear at about 760, 1588, and 1635 cm −1 in BPCACS, which are assigned to the characteristic absorption of benzene and pyridine. [23,32,33] At the same time, 2CBPCACS, 3CBPCACS, 4CBPCACS also show similar absorptions and these data preliminarily demonstrated the successful synthesis of the aimed chitosan oligosaccharide derivatives.…”
Section: Chemical Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,30,31] For derivative CACS, new peaks appearing at 1754 and 790 cm −1 are assigned to C = O and C─Cl groups respectively. [22,32] After the Schiff bases of pyridine-4-aldehyde were grafted, the absorption of C─Cl at 790 cm −1 weakens and new peaks appear at about 760, 1588, and 1635 cm −1 in BPCACS, which are assigned to the characteristic absorption of benzene and pyridine. [23,32,33] At the same time, 2CBPCACS, 3CBPCACS, 4CBPCACS also show similar absorptions and these data preliminarily demonstrated the successful synthesis of the aimed chitosan oligosaccharide derivatives.…”
Section: Chemical Synthesis and Characterizationmentioning
confidence: 99%
“…The peaks in range of 7.7-9.0 ppm are related to the protons of pyridine ring and the peaks at about 6.5-7.6 ppm are the absorption signals of the protons of benzene ring. [23,32] Figure 3 shows the 13 C NMR spectra of COS, CACS, BPCACS, 2CBPCACS, 3CBPCACS, and 4CBPCACS. The carbon signals of chitosan oligosaccharide backbone are observed at 55-100 ppm.…”
Section: Chemical Synthesis and Characterizationmentioning
confidence: 99%
“…In this paper, these substrates demonstrated to be antifungal but not to be completely biocompatible by exhibiting some dose-dependent cytotoxicity. Finally, in 2020, the research group (Figure 4d) used nucleophilic substitution reactions to form urea and pyridine-containing chitosan, and these polymers also proved to be antifungal and also to cause low cytotoxicity on L929 cells with cell viabilities up to 100% (Zhang et al, 2020). For the last two examples, not only antifungal activity was achieved, but also antioxidant and radical scavenging properties.…”
Section: A Final Series Of Examples Of Chitosan Modification Is the Workmentioning
confidence: 99%
“…(Ali & Wilson, 2017;Kariduraganavar et al, 2014;Lee et al, 2004;Lim et al, 2008;Niu et al, 2017). In this work, polyhexamethylene guanidine hydrochloride (PHMGH) was evaluated for its F I G U R E 4 Modified derivatives of chitosan which have shown potentiated antifungal properties (Tan et al, 2017(Tan et al, , 2018Wei et al, 2018;Zhang et al, 2020) F I G U R E 5 Formation of nylon-3 derivatives from ring-opening polymerization of substituted β-lactams antifungal properties (Figure 6). The authors found that this polymer has comparable MICs to AmB against various fungi species (Table 2), while causing no haemolysis or LDH release at concentrations at least up to 16 times higher than the found MICs (in direct contrast with AmB which is much more toxic to human cells).…”
Section: A Final Series Of Examples Of Chitosan Modification Is the Workmentioning
confidence: 99%
See 1 more Smart Citation